Municipal solid waste: A potential source of clean energy for Khartoum State in Sudan. (November 2022) - Farouk, Hazir; Lang, Andrew; Tahir, Furqan; Al-Ghamdi, Sami G.
Abstract: Sudan is a large African country with a land area of 1.882 million km 2 and a population of 43 million people. The country has a fast-growing population, consistent migration from rural to urban areas, raised per-capita demand for power and fuels, and falling fossil-fuel production. Additional baseload or on-demand energy sources are needed to supply the Nile Valley system. The increasing silting of the different hydroelectricity dams is a problem for the future availability of hydroelectricity generation. Non-recyclable combustible municipal solid waste and other urban organic waste streams can be used to provide low-emission baseload electricity and a cost-effective supply of heat for industry. These wastes, which have the potential to be used as feedstocks for energy production, have already been gathered together in enormous quantities. The current landfill disposal method is becoming increasingly expensive, and it leads to several negative environmental impacts, such as methane emissions and air and water pollution. This research looks at how the non-recyclable combustible fraction of waste collected in Khartoum State can be used to generate considerable amounts of energy and industrial heat while reducing the greenhouse gas (GHG) emissions. This might be accomplished by employing and adopting efficient technologies that are extensively used elsewhere in the globe, as well as securing the additional benefits of more permanent jobs, fewer fossil fuel imports, and improved national resource security for Sudan.